2017
DOI: 10.1093/eurpub/ckw261
|View full text |Cite
|
Sign up to set email alerts
|

Education predicts cervical cancer survival: a Lithuanian cohort study

Abstract: : We examined inequalities in cervical cancer survival in Lithuania by education and place of residence. : The study is based on the linked dataset that includes all records of the 2001 population Census, all records from Lithuanian Cancer Registry (cancer incidence) and all death and emigration records from Statistics Lithuania for the period between 6 April 2001 and 31 December 2009. The study group includes cervical cancers registered in the Cancer Registry from 1 January 2002 to 31 December 2006. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…This is the same with the research conclusion of Chinese scholar Wu Ying [24]. Some studies [25][26] have also found that the quality of life of cervical cancer survivors is related to their education level. The higher the education level, the higher the quality of life of patients.…”
Section: Discussionsupporting
confidence: 86%
“…This is the same with the research conclusion of Chinese scholar Wu Ying [24]. Some studies [25][26] have also found that the quality of life of cervical cancer survivors is related to their education level. The higher the education level, the higher the quality of life of patients.…”
Section: Discussionsupporting
confidence: 86%
“…Place of residence (urban vs. rural) is known to be associated with different exposures to certain risk factors ( 19 25 ), differences in access to health services ( 26 , 27 ), and differing survival rates of cancer patients ( 28 30 ). Therefore, we decided to assess health knowledge and health behaviours referred to in the ECAC as well as the availability of health education in a population inhabiting a remote rural area.…”
Section: Introductionmentioning
confidence: 99%
“…This is probably due to the fact that, regarding the continuity of care for patients affected by both DSA and SARS-CoV-2, the number of cases was small, and it was not necessary to create separate pathways and/or wards [14], whereas the continuity of oncological care was, in any case, guaranteed thanks to the use of protective devices, pre-triage of patients accessing the hospital, delay of non-urgent visits, and use of telemedicine for patients' follow-up, in addition to periodical rhino-pharyngeal swabs for SARS-CoV-2 testing in healthcare workers [18][19][20]. It is interesting, however, how the literature reports a gap in the knowledge of palliative care [23] and that a higher education leads to higher chances of survival in some typologies of cancer [24].…”
Section: Discussionmentioning
confidence: 99%